Leonard Sax (2006). Why Gender Matters: what Parents and Teachers Need to Know about the Emerging Science of Sex Differences. New York: Broadway Books, ss. 322 (Przegląd Pedagogiczny, 2008)
Recenzja publikacji: Leonard Sax, Why Gender Matters: what Parents and Teachers Need to Know about the Emerging Science of Sex Differences. New York 2006.